The Influence Of The Board Of Commissioners, Audit Committee, and Ownership On The Performance Of Non-Financial Companies in Indonesia - Juliani, Meily; Emilio, Joben; Candra, Rudi (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
The researcher's investigation centers on the influence of the board of commissioners, audit committee, and ownership on the performance of non-financial companies in Indonesia listed on the Indonesia Stock Exchange (IDX) as the object of research for the period 2018 to 2022. The selection of samples involved 366 data samples using the purposive sampling technique, so 1,830 sample data units were obtained during the five-year research period. Derived from the outcomes of the logistic regression examination conducted with the Eviews 12 application, the results obtained are that the variables of the independent board of commissioners and independent audit committee have a significant adverse effect on the company's performance. Meanwhile, the variable size of the audit committee and committee meetings significantly influence company performance. The remaining variables, such as the size of the board of commissioners, board of commissioners meetings, family ownership, concentration of ownership, and managerial ownership, do not affect the company's performance.